Validity and Reliability Content of Instrument of Assessments Mengalihaksarakan Serat Wulangreh Pupuh Gambuh Class VIII - Lisufiana, Desi; Supriyanto, Teguh; Khumaedi, Muhammad (Universitas Negeri Semarang, 2019)
The factual situation of school is the absence of a raw Javanese character assessment instrument that is backed by this research. The purpose of research is to know the validity level and the efficacy of the assessment instrument, which is the ability to use a mengalihaksarakan serat wulangreh pupuh gambuh to make the teacher in the assessment more objective, for the researchers need to conduct the validity test of the content and reliability of the interrater against the instrument used. The method used is a quantitative description using 3 expert judgment, one of teachers’ Javanese language teachers are from SMP N 1 Brangon and SMK ma'arif NU 01 Semarang and member of the expert instrument development is the graduate lecturer in Semarang State University. The researchers use the validation instrument to obtain its data by providing a checklist of aspects that have been created by researchers with 4 categories that are appropriate, appropriate, inappropriate, and not appropriate. The data is then analysed using the Aiken V formula to determine the level of validity and the instrument, and to know the consistent data then the reliability test is carried out using Two Way Anova with the help of SPSS version 16.0 application that continued calculations using HOYT formula. The result of the content validation analysis shows the value above 0.3 which means all aspects assessed by experts are valid. The reliability test using the formula Hoyt obtained the value of 0702 means that all aspects assessed by 3 expert judgment have a degree. The assessment instrument is mengalihaksarakan serat wulangreh pupuh gambuh a after tested the validity of the contents and reliability of valid and reliable.